The determinants of working capital management practices Malaysian perspective - Mohd Ridzuan, Darun (2012)
Purpose of research - this study examines the practice of Working Capital Management (WCM) in an organizational context,specifically Malaysian listed companies.Even though many studies of WCM have been undertaken in many countries around the world, the understanding of WCM practices in an organizational context has neither been adequately documented nor understood.Scholars have largely concentrated on developing sophisticated financial models, however managers need easy to use models (Gitman, Moses,& White, 1979).In the event of changes in organizational context,it is argued that the failure of WCM research to reflect the characteristics and challenges of contemporary organizational settings has led to a lack of understanding and gives rise to the need for a conceptual framework explaining current WCM practices.This study intends to first develop an understanding of the determinants of the various WCM practices currently used in organizations;and secondly to develop a conceptual framework explaining the dynamics of WCM in a Malaysian context.Design and methodology - this research used multiple-case studies of five Malaysian companies listed on the main board of Bursa Malaysia.Key informants, representing various functional areas and hierarchical levels,were interviewed to gained insights about how working capital components were managed within the organizational context.The semistructured interviews were designed to explore the diversity of WCM practices.Data was analyzed using qualitative methods to gain rich narratives and in-depth understanding of WCM practices for each case, then, cross case analysis enabled this research to develop a conceptual framework.